Hepatoprotective effect of bone marrow-derived mesenchymal stromal cells in CCl(4)-induced liver cirrhosis - Aithal, Ashwini P. (3 Biotech, 2021)
Bone marrow mesenchymal stromal cells (BM-MSCs) are multipotent stem cells which are ideal candidates for use in regenerative medicine. The objectives of this study were to evaluate the hepatoprotective effect of BM-MSC and its combination treatment with silymarin in carbon tetrachloride (CCl(4))-induced liver cirrhosis animal model and to investigate whether tail vein or portal vein infusion was the ideal route for BM-MSC transplantation. 36 female Wistar rats were randomly divided into six groups (n = 6): Group 1 (normal control), Group 2 (received only CCl(4), disease model), Group 3 (CCl(4) + BM-MSCs through tail vein), Group 4 (CCl(4) + BM-MSCs through portal vein), Group 5 (CCl(4) + silymarin), Group 6 (CCl(4) + BM-MSCs + silymarin). On the 21st day after treatment, blood samples were collected for biochemical estimations. After the experiment, the rats were sacrificed. Liver was dissected out and processed for histopathology and scanning electron microscopy studies. Liver enzyme and marker analysis, histopathological studies indicated that the combination of BM-MSCs and silymarin was effective in treating liver cirrhosis. Transplanted BM-MSCs in combination with silymarin ameliorated the liver tissue damage through their immunoregulatory activities. Among the two routes, the intravenous administration of cells through the tail vein was found to be more effective and safe.